COMPARATIVE ANALYSIS OF THE EFFECTIVENESS OF OLD AND NEW TB DRUGS IN THE TREATMENT OF PULMONARY TUBERCULOSIS - Romauli Lumbantobing; Linggom Kurniaty; Welly Salutondok; Tiroy Sari B. Simanjuntak (SYNTHESIS Global Health Journal, 2025)
Background. The availability of effective drug regimens of Pulmonary tuberculosis (TB) poses a global health challenge. Traditional first-line therapies-isoniazid, rifampicin, pyrazinamide, and ethambutol-remain the cornerstone of TB management due to their accessibility and documented cure rates exceeding 85%. Nevertheless, limitations such as variable drug metabolism, patient non-adherence, and the emergence of multidrug-resistant strains have prompted evaluation of newer treatment combinations to optimize efficacy, safety, and duration. The purpose was to compare the effectiveness of older first-line tuberculosis (TB) drug regimens with newer therapeutic regimens in the treatment of pulmonary tuberculosis. Research Method. This narrative review synthesizes findings from five peer-reviewed studies comparing the effectiveness and safety profiles of conventional and novel TB drug regimens. The review focused on regimen composition, treatment duration, bacteriological clearance, hepatotoxicity, and patient adherence outcomes. Findings. The inclusion of pyrazinamide in six-month regimens significantly accelerated bacterial clearance without increasing hepatic toxicity compared to traditional nine-month isoniazid–rifampicin regimens. Additionally, shorter rifampin-based regimens for latent TB demonstrated higher treatment completion rates and fewer adverse effects than isoniazid monotherapy. Emerging regimens, such as fluoroquinolone-based HRM therapies and the novel BPaL combination (bedaquiline, pretomanid, and linezolid), yielded comparable or improved outcomes, with BPaL achieving success rates up to 93% in drug-resistant TB cases. Conclusion. Current evidence supports the strategic adaptation of TB therapy to balance efficacy, tolerability, and treatment duration. Incorporating newer drug combinations, particularly for drug-resistant TB, enhances adherence and clinical outcomes, underscoring the need for individualized treatment protocols aligned with evolving resistance patterns and patient profiles.